Athletes' perceived level of risk associated with botanical food supplement use and their sources of information - McDaid, B.; Wardenaar, F. C.; Woodside, J. V.; Neville, C. E.; Tobin, D.; Madigan, S.; Nugent, A. P. (International Journal of Environmental Research and Public Health, 2024)
Athletes should carefully consider the use of botanical food supplements (BFSs) given the current lack of substantiation for botanical nutrition and health claims under EU and UK food laws. In addition, athletes may be at an increased risk of doping violations and other adverse outcomes potentially associated with BFS use; however, little is known about athletes` intake, knowledge, or perceptions in relation to BFS use. An online cross-sectional survey of n = 217 elite and amateur athletes living on the island of Ireland was conducted using Qualtrics XM to assess intake, knowledge, attitudes, and perceptions. General food supplements (FSs) were reported by approximately 60% of the study cohort, and 16% of the supplements reported were categorized as BFS. The most frequently consumed BFSs were turmeric/curcumin (14%), Ashwagandha (10%), and Beetroot extract (8%). A higher proportion of amateur athletes would source information about BFSs from less credible sources, such as fellow athletes, or from internet sources or their coach, compared to elite athletes. Those who sourced information about botanicals from fellow athletes (p = 0.03) or the internet (p = 0.02) reported a lower perceived level of risks associated with BFS use. This study therefore suggests that amateur athletes may be more likely to source information from less credible sources compared to elite athletes who may have more access to nutrition professionals and their knowledge/advice. This may have potential adverse implications for amateur athletes, e.g., Gaelic games players, who are included within the doping testing pool but who may not have access to evidence-based nutrition advice.